Aerodynamic roughness of rippled beds under active saltation at Earth-to-Mars atmospheric pressures - Carlos A. Alvarez; Mathieu G. A. Lapôtre; Christy Swann; Ryan C. Ewing; Pan Jia; Philippe Claudin (Nature Communications)
Abstract As winds blow over sand, grains are mobilized and reorganized into bedforms such as ripples and dunes. In turn, sand transport and bedforms affect the winds themselves. These complex interactions between winds and sediment render modeling of windswept landscapes challenging. A critical parameter in such models is the aerodynamic roughness length, z 0, defined as the height above the bed at which wind velocity predicted from the log law drops to zero. In aeolian environments, z 0 can variably be controlled by the laminar viscous sublayer, grain roughness, form drag from bedforms, or the saltation layer. Estimates of z 0 are used on Mars, notably, to predict wind speeds, sand fluxes, and global circulation patterns; yet, no robust measurements of z 0 have been performed over rippled sand on Mars to date. Here, we measure z 0 over equilibrated rippled sand beds with active saltation under atmospheric pressures intermediate between those of Earth and Mars. Extrapolated to Mars, our results suggest that z 0 over rippled beds and under active saltation may be dominated by form drag across a plausible range of wind velocities, reaching values up to 1 cm—two orders of magnitude larger than typically assumed for flat beds under similar sediment transport conditions.